Revitalisasi Maqasid al-Shari’ah dalam Pengembangan Ekonomi Syariah di Indonesia (Studi Kasus atas Fatwa-fatwa DSN-MUI Tahun 2000-2006) - M. Atho Mudzhar (JURNAL INDO-ISLAMIKA, 2014)
The author examines the concept of Maqasid al-Shari’ah that was used or revitalized as arguments for 53 legal opinions (fatwas) of Dewan Syariah Nasional (DSN) of the Indonesian Ulama Councils (MUI) issued during 2000-2006. Because the purpose of the Maqasid al-Shari’ah is for public interests (maslaha), the examination of the Maqasid al-Shari’ah was conducted by observing the application of fiqh principles in DSN-MUI fatwas, particularly those that related to maslaha. The study found that 50 of 53 fatwas of DSN-MUI included the fiqh principles in all judgments, despite of being equipped by basic Islamic reasoning principles such as Al-Quran, Hadis, Ijma’ and Qiyas. There are 11 possible fiqh principles for use in all fatwas, the minimum is one principle and the maximum is five principles. Overall, the fiqh principles were used 134 times. This means that the average use of the fiqh principles is 2.5 in every fatwa. The most used fiqh principle was the axiom stating that the basic legal principle for muamala is permissible as long as no proposition/law forbids it. The general principle is often used without other specific supporting principles. It should be noted that the DSN-MUI legal opinions tend to be permissive or liberal and less accurate (wijhat al-nazar), despite their validity.